COMPLEMENTARY THERAPY THAT EFFECTS ON REDUCING BLOOD SUGAR LEVELS IN DIABETES PATIENTS IN INDONESIA: LITERATURE REVIEW - Ernawati, Ernawati; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
Complementary therapies refer to various treatment methods that complement conventional medical approaches, including nature-based practices, relaxation techniques, and holistic approaches that emphasize physical, mental, and emotional balance. This research aims to provide deeper insight into the role of complementary therapies in diabetes management in Indonesia. Research Method uses the literature review method by searching for articles in this literature review using the Mendeley and Google Scholar databases (2019-2023). The results of this study showed boiled water (bitter melon, gambas vegetables, boiled water from guava leaves, boiled cherry leaves, jicama starch essence, herbal tea from bay leaves and red ginger, boiled water from acacia leaves), Benson relaxation, foot reflexology massage and foot exercises, Acupressure, yoga, hydrotherapy, and aromatherapy show significant results in reducing blood sugar levels in diabetes patients. Conclusion: From this literature review, seven complementary therapies can be used and are trusted to reduce blood sugar levels in diabetes patients in Indonesia. Keywords: Complementary Therapy, Diabetes, Indonesia.